Mobile application for care and health control of camelids - Roberto Demmis Muñoz Villacorta; Carlos Manuel Oscco Aguero; Laberiano Andrade-Arenas (Institute of Advanced Engineering and Science, 2023)
Due to the events caused by COVID-19, several activities were paralyzed, such as the export of camelids. In the present study, it was observed that many of the camelids that are located in the highest of the Andes, are exposed to diseases that originate from climatic changes or from the infrastructure in which they are inhabiting. For this reason, the veterinary mobile application for camelids was implemented, which will help care as well as sanitary control, this application was developed through the agile scrum methodology, since it adapts to the various modules used, which would be consulta of diseases, recommendations for breeding and contacts with veterinary experts. As a result, the optimal mobile application was obtained for the needs of the people who live in that sector. In addition, it made it easier for the farms, as well as for the people who are in the frozen areas, so that they have better care and control of this species of animals, since the camelids are part of the fauna of the Andes and above all all its fiber and its derivatives are exported, which generates great economic sustenance for that sector.